Designing Organizations for Collaborative Relationships: the Amenability of Social Capital to Inter-Agency Collaboration in the Graduate Employment Context in Uganda - Ntale, Peter Dithan; Ssempebwa, Jude (Employee Responsibilities and Rights Journal, 2022)
This paper discusses organizational social capital with the view that its amenability to collaboration creates trust, mutuality and reciprocal relational values upon which organizations may synchronize their efforts to create graduate employment opportunities. We adopted a cross-sectional survey design with both quantitative and qualitative approaches. We conveniently collected data from staff and leaders of four organizations which were purposely selected to represent a cross-section of government, private and civil society organizations whose mandate touches on the employability of university graduates in the country in very direct ways. From a sample of 175 respondents, we received 105 filled questionnaires, representing a response rate of 62%. We observed that the extent to which the social capital components of trust, mutuality and reciprocal relations were amenable to interagency collaboration were low to sufficiently permit collaborative relationships upon which synergy between agencies would enhance the creation of graduate employment opportunities. The implication of this study is that we have been trained to foster self-sufficiency, individual competence, individual brilliance and independence through the pursuance of individual goals and actions. This greatly affects the trust, mutuality and reciprocal relationships that people/organizations develop with one another, consequently denying societies or organizations the opportunity to tap into the synergistic capital that would help people or organizations tackle the challenges that are beyond their individual capabilities.
Keywords: Trust; Reciprocity; Mutuality; Collaboration; Graduate employment